Uptake of same-day initiation of HIV treatment in Malawi, South Africa, and Zambia as reported in routinely collected data: the SPRINT retrospective cohort study [version 2; peer review: 1 approved, 3 approved with reservations] - Bevis Phiri; Alana T. Brennan; Lloyd Mulenga; Timothy Tcherini; Hilda Shakwelele; Prudence Haimbe; Andrews Gunda; Bilaal Wilson Matola; Rose Nyirenda; Sydney Rosen; Kamban Hirasen; Amy Huber (Gates Open Research, 2023)
Background: Since 2017 global guidelines have recommended “same-day initiation” (SDI) of antiretroviral treatment (ART) for patients considered ready for treatment on the day of HIV diagnosis. Many countries have incorporated a SDI option into national guidelines, but SDI uptake is not well documented. We estimated average time to ART initiation at 12 public healthcare facilities in Malawi, five in South Africa, and 12 in Zambia. Methods: We identified patients eligible to start ART between January 2018 and June 2019 from facility testing registers and reviewed their medical records from HIV diagnosis to the earlier date of treatment initiation or 6 months. We estimated the proportion of patients initiating ART on the same day or within 7, 14, 30, or 180 days of baseline. Results: We enrolled 825 patients in Malawi, 534 in South Africa, and 1,984 in Zambia. Overall, 88% of patients in Malawi, 57% in South Africa, and 91% in Zambia received SDI. In Malawi, most who did not receive SDI had not initiated ART ≤6 months. In South Africa, an additional 13% initiated ≤1 week, but 21% had no record of initiation ≤6 months. Among those who did initiate within 6 months in Zambia, most started ≤1 week. There were no major differences by sex. WHO Stage III/IV and tuberculosis symptoms were associated with delays in ART initiation;  clinic size and having a CD4 count done were associated with an increased likelihood of SDI. Conclusions: As of 2020, SDI of ART was widespread, if not nearly universal, in Malawi and Zambia but considerably less common in South Africa. Limitations of the study include pre-COVID-19 data that do not reflect pandemic adaptations and potentially missing data for Zambia. South Africa may be able to increase overall ART coverage by reducing numbers of patients who do not initiate ≤6 months.